Left renal vein nutcracker syndrome and concurrent IVC duplication: Surgical treatment - Eric Midenberg (Urology Case Reports, 2021)
Multiple vascular anomalies may be encountered in patients with nutcracker syndrome; further compounding the surgical complexity in managing this condition. A 28-year-old male presented with persistent flank pain and hematuria. Imaging revealed narrowing of the left renal vein at the aortomesenteric junction, and a dilated vein consistent with the left gonadal vein. On surgical exploration, a duplicated IVC was found. The patient underwent a right caval-to-left caval bypass using a cryopreserved femoral vein homograft. The surgery was well tolerated and completely resolved the patient's symptoms.